Biodegradable wet-spun fibers modified with antimicrobial agents for potential applications in biomedical engineering - Felgueiras, Helena Prado (2021)
Wet-spinning is a non-solvent induced phase inversion technique that allows the production of continuous polymeric microfibers, with a uniform morphology, based on the principle of precipitation. It allows the production of 3D fibrous constructs with an intricated architecture that facilitates cell infiltration, something that is very limited in electrospun nanofibrous mats, thus increasing its interest in biomedicine. Wet-spun scaffolds are also more easily processed and can be loaded with a variety of biomolecules of interest. Antimicrobial agents that display a broad spectrum of activity against bacteria, fungi and viruses have been combined with such constructs demonstrating great potential to fight infections. In the present work, we explore the use of wet-spinning to process both natural and synthetic biodegradable polymers in the form of microfibers, and the necessary processes to modify their surface to increase their antimicrobial profile. The synergistic potential of specialized biomolecules within wet-spun fibrous architectures are also highlighted.